2012
DOI: 10.1257/pol.4.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Green Infrastructure: The Effects of Urban Rail Transit on Air Quality

Abstract: The transportation sector is a major source of air pollution worldwide, yet little is known about the effects of transportation infrastructure on air quality. In this paper we measure the effects of one major type of transportation infrastructure -urban rail transit -on air quality. Our approach uses the sharp discontinuity in transit utilization on the opening day of a completely new rail transit system in Taipei, Taiwan to identify the air quality effects of rail transit infrastructure.Using hourly air quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
140
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(151 citation statements)
references
References 51 publications
(54 reference statements)
8
140
1
2
Order By: Relevance
“…Winston and Shirley (1998) found that policies to induce those shifts were not effective because transit also produces pollution and operates with a low load factor and small mode share. Chen and Whalley (2012) used the opening of a new metro station in Taipei as an exogenous event to estimate the effect of urban rail transit on air quality and found that it reduced one key tailpipe pollutant, carbon monoxide, 5-15 percent, but it had no effect on ground level ozone pollution.…”
mentioning
confidence: 99%
“…Winston and Shirley (1998) found that policies to induce those shifts were not effective because transit also produces pollution and operates with a low load factor and small mode share. Chen and Whalley (2012) used the opening of a new metro station in Taipei as an exogenous event to estimate the effect of urban rail transit on air quality and found that it reduced one key tailpipe pollutant, carbon monoxide, 5-15 percent, but it had no effect on ground level ozone pollution.…”
mentioning
confidence: 99%
“…Yoshino and Abidhadjaev (2015) provide some evidence that a newly built railway in south Uzbekistan may have caused 0.4%~2.0% GDP growth in the regions affected. Finally, Chen and Whalley (2012) show that the opening of the new rail transit system in Taipei,China reduced air pollution from carbon monoxide, a key tailpipe pollutant, by 5%-15%. The results highlight the importance of urban public railway transit infrastructure.…”
Section: Infrastructure and Its Role In Developmentmentioning
confidence: 99%
“…Two recent studies have provided an initial look at the relationship between transit supply and air quality. Using hourly air quality data from Taipei [31], find that the new rail system's opening reduced carbon monoxide by 5-15% but had little effect on ground level ozone pollution [4,31]. In their analysis of the environmental effect of expanded rail service in Germany over the period 1994-2004 [32], find that increases in rail service frequency lead to a reduction in some pollutants (NO, NO 2 , and CO), though not others (SO 2 and O 3 ) [4,32].…”
Section: Air Qualitymentioning
confidence: 99%